SIGMAR1 variants in ALS–PD complex cases: a case report of a novel mutation and literature review - Li, Haining; Xuan, Tingting; Xu, Ting; Yang, Juan; Cheng, Jiang; Wang, Zhenhai (Frontiers in Neurology, 2023)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease characterized by progressive degeneration of upper and lower motor neurons, with occasional involvement of the extrapyramidal system. Mutations in the sigma non-opioid intracellular receptor 1 (SIGMAR1) gene have been identified as one of the causes of ALS. Here, we present a case of a 49-year-old man diagnosed with ALS–Parkinson’s disease (PD) complex. The patient exhibited bradykinesia and tremor, and whole-exome sequencing revealed homozygous mutations in the SIGMAR1 gene (c.446-2A > T). In addition, we conducted an investigation into the clinical and molecular phenotype of previously reported variants of SIGMAR1 associated with ALS. This case report aims to raise awareness among physicians regarding atypical phenotypes of amyotrophic lateral sclerosis and to encourage further research on the factors leading to SIGMAR1 mutations in patients.